2001
DOI: 10.1161/01.cir.104.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Plays a Critical Role in the Development of Pressure Overload–Induced Cardiac Hypertrophy

Abstract: These results suggest that calcineurin plays a critical role in the development of pressure overload-induced cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 24 publications
4
73
0
Order By: Relevance
“…neural) effects of calcineurin suppression. Similar results were recently reported using other transgenic approaches (14,15).…”
Section: Discussionsupporting
confidence: 91%
“…neural) effects of calcineurin suppression. Similar results were recently reported using other transgenic approaches (14,15).…”
Section: Discussionsupporting
confidence: 91%
“…Histological analysis of the heart tissue was performed according to previously described methods (16). Ventricular sections were stained with H&E for routine histological examination.…”
Section: Animalmentioning
confidence: 99%
“…Aortic banding. Suprarenal aortic banding was produced as previously described (16). Briefly, under ketamine anesthesia (100 mg/kg, i.p.…”
Section: Introductionmentioning
confidence: 99%
“…Gain-and loss-of-function studies in genetically altered mice and cultured cardiomyocytes have demonstrated the sufficiency and necessity of calcineurin to regulate pathological cardiac hypertrophy (5)(6)(7)(8)(9)(10)(11)(12). In contrast, in vivo confirmation about the involvement of its direct downstream transcriptional effectors in the heart is still incompletely resolved.…”
mentioning
confidence: 99%